Women’s abuse experiences in Jordan: A comparative study using rural and urban classifications - Rula Odeh Alsawalqa (Humanities & Social Sciences Communications, 2021)
Abstract This study explored the patterns of economic abuse among working married women from rural and urban areas in Jordan, and identified their experiences with other abuses interconnected with economic abuse, including psychological, emotional, and physical abuse and harassment. A quantitative research approach using a descriptive comparative design was employed. The findings indicated that 55.5% of urban and 44.5% of rural women have encountered spousal economic abuse in two ways: (1) controlling their economic resources and managing their financial decisions and (2) exploiting their economic resources. Economic abuse was found to be intertwined with other forms of abuse; women who faced economic abuse also endured primarily emotional and psychological abuse, followed by physical abuse and harassment, as tactics to reinforce economic abuse and maintain control over them. The most common form of psychological abuse was being made to feel frustrated and neglected when requesting emotional support, while emotional abuse was typified by resentment and being told they are inadequate. Physical abuse included partners shaking, slapping, or throwing objects at them. Both rural and urban women reported being harassed at their workplace by their partners’ repeated phone calls. In general, urban women faced more economic and other forms of abuse than rural women, especially emotional and physical abuse.